The Role of Incomplete Information and Others' Choice in Reducing Traffic: A Pilot Study - Romano, Angelo; Mosso, Cristina O.; Merlone, Ugo (Frontiers in Psychology, 2016)
In this study, we investigate the role of payoff information and conformity in improving network performance in a traffic dilemma known as the Braess paradox. Our goal is to understand when decisions are guided by selfish motivations or otherwise by social ones. For this purpose, we consider the manipulation of others’ choice, public and private monitoring and information on distribution of choices. Data show that when social comparison was not salient, participants were more cooperative. By contrast, cooperativeness of others’ choice made participants more competitive leading to traffic and collective performance decrease. The implications of these findings to the literature on social dilemmas are discussed.